Perkembangan Morfo-anatomi Bunga, Buah, dan Biji Nyamplung (Calophyllum inophyllum L), Sebagai Tanaman Penghasil Biodisel: Morpho-Anatomy Development of Flower, Fruit and Seed of Nyamplung ( Calophyllum inophyllum L) as Biodiesel-Producing Plant - Hamim; Romadlon, Zahrul; Dorly (Departemen Biologi, Institut Pertanian Bogor, 2019)
Nyamplung (Calophyllum inophyllum), a non-edible producing plant, is a tropical plant traditionally used by local residents as firewood, building material and medicinal plants. The research aimed to study the development of flower and fruit as well as oil content of nyamplung seeds. Two adult trees (P1 and P2) with different provenance were used in experiment. Morphology of flower and fruit, and seed germination were observed from the field, while the microscopic anatomical observations and oil content analysis were carried out in the laboratory. The result showed that a single generative bud generally had 8-15 flowers. The flower was arranged in bunches, with 4 petals, 4 sepals, single pistil and 4 files of anthers surrounded the pistil. In some cases, the flowers had 5 sepals, or 3 sepals and 3 anthers files. Fruits were round, green and turned to harden with brownish color during maturation. Flower bud grown from bud was ready to blossom 27 days after initiation (DAI). There were up to 48.52% flower buds drop at 24 DAI, and they were still increase up to 64.5% flower drop during the whole of flower development. The observation also showed that fruit drop rate of P2 plant was higher than P1. After flower bloom for 3 or 4 days after anthesis, the flowers started to lose their parts. The fruits started to ripe 8-10 week after anthesis (WAA). Seeds from P2 tree had oil content of 51.79%, which was higher than the P1 tree (42.57%).